Bioflok sebagai Solusi Mengatasi Permasalahan Lingkungan untuk Akuakultur Masa Depan Berkelanjutan : Sebuah Tinjauan - Rini Marlida (Rawa Sains: Jurnal Sains STIPER Amuntai, 2020)
Aquaculture is currently the foundation of the world's animal protein provider. The sustainability of this sector is greatly influenced by business governance which must prioritize environmentally friendly aspects. Nutrient enrichment waste and the spread of fish and other aquatic organisms are significant issues present in aquaculture systems throughout the world today, especially intensive aquaculture. The purpose of writing this article is to provide an overview of biofloc as a solution in overcoming environmental problems for a sustainable future aquaculture. Intensive aquaculture applies high density maintenance and artificial feeding. The system leads to environmental problems because a large amount of waste produced contains solids and nutrients that accumulate into pollutants that cause eutrophication and toxins for aquatic organisms. Biofloc technology is a new approach to reduce the waste of aquaculture activities. In this system, heterotrophic bacteria and algae are grown together in flocks under controlled conditions with no or minimal water exchange. Biofloc is a nutrient package that can be utilized directly by farm animals. Biofloc also acts as biocontrol. Biofloc technology can help overcome problems in intensive aquaculture.